Marandu palisade grass management strategies at the beginning of the deferment period and effects on tillering - Santos, Manoel Eduardo Rozalino; Ávila, Amanda Bortoleto; De Carvalho, Angélica Nunes; De Oliveira Rocha, Gabriel; De Oliveira Scarpino Van Cleef, Flavia [UNESP]; Segatto, Bruno Nascimento; Vasconcelos, Kathleen Alves; Pereira, Rayne Souza (Universidade Estadual de Londrina, 2018)
Pasture mowing at the beginning of deferment stimulates tillering and can be used in different ways. The aim of this study was to understand how the mowing of Urochloa brizantha cv. Marandu Syn. Brachiaria brizantha cv. Marandu (marandu palisade grass) prior to the deferment period modifes tillering activity and the characteristics of young, mature, and old tillers. Three mowing strategies were evaluated: canopies kept at a height of 15 cm for fve months before deferment (15/15 cm); canopies kept at 30 cm (30/15 cm) or 45 cm (45/15 cm) for fve months before deferment and posteriorly cut to 15 cm at the start of the deferment period. The structural characteristics of young, mature, and old tillers of marandu palisade grass were compared only at the end of the deferment period. The tiller appearance rate was greater before (16.0%) than during (6.4%) the deferment period, but a contrasting response pattern was observed for the tiller mortality rate. The defoliation strategies that resulted in greater numbers of tillers in the canopies were 30/15 cm (2,098 tillers m-2) and 45/15 cm (2,160 tillers m-2). The defoliation strategy that generated the greatest percentage of young tillers in the canopy was 45/15 cm (26.1%), while the percentage of old tillers was greater in the canopies submitted to the 15/15 cm (64.1%) and 30/15 cm (61.5%) strategies. Weight and percentage of live stems of mature and old tillers were greater in relation to young tillers. The percentage of live leaves was grater in young tillers (52.6%), intermediate in mature tillers (41.4%), and lower in old tillers (21.3%). Regarding the percentage of dead leaves, the opposite trend was observed, where the percentage was greater in the old than in young tillers. Leaf area was greater in mature tillers (55.3 cm2) than in old tillers (29.2 cm2). Mowing of the marandu palisade grass to 15 cm at the beginning of the deferment period increases the number of young tillers, which have a more favorable morphological composition than mature and old tillers.
Keywords: Dynamics of tillering; Morphological composition; Tillers; Urochloa brizantha